The science of speed: Determinants of performance in the 100 m Sprint - Commentary and response to commentary - Majumdar, A. S.; Robergs, R. A.; Pitsiladis, Y.; Davis, A.; Johnson, D. (International Journal of Sports Science and Coaching, 2011)
Performance in the 100 m sprint is influenced by a multitude of factors including starting strategy, stride length, stride frequency, physiological demands, biomechanics, neural influences, muscle composition, anthropometrics, and track and environmental conditions. The sprint start, the accelerative phase of the race, depends greatly on muscular power. Three considerations of the sprint start are reaction time (time to initiate response to the sound of the starting gun), movement time (onset of response until end of movement) and response time. Maximal velocity running is a result of stride length and stride frequency. While stride length can be greatly limited by an individual's size and joint flexibility, stride frequency can be affected by muscle composition, neuromuscular development, and training. Although 100 m sprint world record times have progressed drastically, there is limited evidence for how technology has contributed to such improvement. As such, human physiology and physique combine to be the most influential determinants of improved sprint performance.